2005
DOI: 10.3168/jds.s0022-0302(05)73028-9
|View full text |Cite
|
Sign up to set email alerts
|

Milk and Cheese Fatty Acid Composition in Sheep Fed Mediterranean Forages with Reference to Conjugated Linoleic Acid cis-9,trans-11

Abstract: Two experiments were undertaken to evaluate the effect on milk and cheese fatty acid composition of feeding different fresh forages to dairy sheep both in winter (experiment 1, growing stage of the forages, early lactating ewes) and in spring (experiment 2, reproduction stage of the forages, midlactating ewes). Four forage species were compared: annual ryegrass (RY, Lolium rigidum Gaudin), sulla (SU, Hedysarum coronarium L.), burr medic (BM, Medicago polymorpha L.), and a daisy forb (CH, Chrysanthemum coronari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
93
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 29 publications
12
93
1
6
Order By: Relevance
“…Except for pelvic fat, in this study there were no significant differences between the atherogenicity index in goat kid from organic or conventional managed dams. There are no known values of this index in studies of goats, nevertheless, the index values for both groups were lower that those reported in milk of sheep fed Mediterranean forages (Addis et al, 2005). The low fat content and FA profile (especially the PUFA content and the n-6:n-3 PUFA ratio) of meat from kids reared in both production systems indicates the beneficial characteristics of this meat with respect to human health.…”
Section: Discussionmentioning
confidence: 63%
“…Except for pelvic fat, in this study there were no significant differences between the atherogenicity index in goat kid from organic or conventional managed dams. There are no known values of this index in studies of goats, nevertheless, the index values for both groups were lower that those reported in milk of sheep fed Mediterranean forages (Addis et al, 2005). The low fat content and FA profile (especially the PUFA content and the n-6:n-3 PUFA ratio) of meat from kids reared in both production systems indicates the beneficial characteristics of this meat with respect to human health.…”
Section: Discussionmentioning
confidence: 63%
“…Actually, sheep cheese is naturally rich in CLA because it is made with milk from grazing ewes. In fact, it is well known from the literature that it is possible to manipulate the fatty acid profile of sheep dairy products, in a higher extent than that of the cows, to maximize the content of beneficial fatty acids by the use of appropriate fresh forage-based regimens [13]. CLA has been recently reported to have antiatherogenic and antineoplastic properties [4e6].…”
Section: Discussionmentioning
confidence: 99%
“…In any case, responses at both time points may be attributed to the effect of sainfoin on ruminal lipid metabolism, given that the inhibition of trans C18 saturation would accumulate vaccenic acid and trans-11 cis-15 18:2, but a negative influence on the first BH steps would decrease their production. This latter response, linked to a lower or slower disappearance of dietary PUFA, appears to better reflect the in vivo effects reported for other tannin-rich legumes, such as the lower milk proportion of trans-11 18:1 and cis-9 trans-11 CLA together with increases in 18:3n-3 and 18:2n-6 in ewes fed sulla (Addis et al, 2005;Cabiddu et al, 2009). In line with this, Turner et al (2005) pointed toward a general inhibition of BH, and not only on the last step, when examining the effects of Lotus corniculatus in- Sainfoin, fatty acid biohydrogenation and ruminal fermentation tation and compromise its practical application in ruminant feeding.…”
Section: Ruminal Biohydrogenationmentioning
confidence: 98%